Some urban facts of life: implications for research and policy - Ruel, Marie T.; Haddad, Lawrence James; Garrett, James L. (International Food Policy Research Institute, 1999)
This review of recent literature explores the challenges to urban food and nutrition security in the rapidly urbanizing developing world. The premise of the manuscript is that the causes of malnutrition and food insecurity in urban and rural areas are different due primarily to a number of phenomena that are unique to or exacerbated by urban living. These areas include (1) a greater dependence on cash income; (2) weaker informal safety nets; (3) greater labor force participation of women and its consequences for child care; (4) lifestyle changes, particularly diet and exercise patterns; (5) greater availability of public services, but questionable access by the poor; (6) greater exposure to environmental contamination; and (7) governance by a new, possibly nonexistent, set of property rights. The main focus is on identifying what is different about urban areas, so as to better frame the program and policy responses.